Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1158/1078-0432.ccr-10-0501
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin Regulation by Estradiol in Breast Tissue: Tamoxifen Inhibits Angiogenin Nuclear Translocation and Antiangiogenin Therapy Reduces Breast Cancer Growth In vivo

Abstract: Purpose: Angiogenin, a 14.2-kDa polypeptide member of the RNase A superfamily, has potent angiogenic effects. Nuclear accumulation of angiogenin is essential for its angiogenic activity. Increased angiogenin expression has been associated with the transition of normal breast tissue into invasive breast carcinoma. In this article, we investigated whether estradiol (E 2 ) affected angiogenin in breast tissue.Experimental Design: We used microdialysis for sampling of extracellular angiogenin in vivo. In vitro cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 41 publications
(49 reference statements)
4
29
0
Order By: Relevance
“…#P000127, 10-mm; refs. 25,26). Catheters, connected to a pump (CMA 107; CMA Microdialysis AB), were perfused with 154 mmol/liter NaCl and 60 g/liter hydroxyethyl starch (Voluven; Fresenius Kabi AB; cat.…”
Section: Microdialysis Of Patientsmentioning
confidence: 99%
“…#P000127, 10-mm; refs. 25,26). Catheters, connected to a pump (CMA 107; CMA Microdialysis AB), were perfused with 154 mmol/liter NaCl and 60 g/liter hydroxyethyl starch (Voluven; Fresenius Kabi AB; cat.…”
Section: Microdialysis Of Patientsmentioning
confidence: 99%
“…One microdialysis catheter was placed in the upper lateral quadrant of the left breast and directed toward the nipple as previously described 5,7,8,34,[43][44][45][46][47][48] and one reference catheter was placed in abdominal subcutaneous fat. Microdialysis catheters (71/M Dialysis AB, Stockholm, Sweden), which consists of a tubular dialysis membrane (length 20 mm, diameter 0.52 mm, and 100,000 atomic mass cut-off) glued to the end of a double-lumen tube (80 mm long £ 0.8 mm in diameter), were inserted via a splitable introducer (M Dialysis AB), connected to a microinfusion pump (M Dialysis AB) and perfused with NaCl 154 mmol/L and hydroxyethyl starch 60 g/L (Voluven Ò , Fresenius Kabi, Uppsala, Sweden), at a perfusion rate of 0.5 mL/min.…”
Section: Microdialysis Proceduresmentioning
confidence: 99%
“…Nuclear accumulation of angiogenin, a member of the RNase superfamily, is essential for angiogenic activity and its increased expression may transform normal breast tissue into invasive carcinoma. Angiogenin is stimulated by E2 and counteracted by the ER antagonist tamoxifen (Nilsson et al, 2010). Using breast cancer cell lines, Harfouche et al (2011) showed a negative correlation between the expression of angiopoietin -1, a ligand for the endothelial tyrosine kinase receptor Tie-2, and levels of ERa and a positive correlation with angiogenesis.…”
Section: Endothelial Cells and Angiogenesismentioning
confidence: 97%